Review of Wireless Charging of EV - Sikandar, Muhammad Salman; Darwish, Mohamed K.; Marouchos, Christos (My University, 2022)
Electrified transportation will minimise greenhouse gas emissions while also lowering gasoline prices. To encourage the adoption of electrified transportation, a variety of charging networks must be established in a user-friendly environment. WEVCS (wireless electric vehicle charging systems) could be a viable alternative technology for charging electric vehicles (EVs) without the need for a plug. The work done in the area of wireless power transfer technology for electric vehicles is described in this paper.
Keywords: Charging (batteries); Energy transfer; Gas emissions; Inductive power transmission